2012
DOI: 10.3844/ajisp.2012.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-10 in Urinary Bladder Carcinoma and Bacillus Calmette-Guerin Immunotherapy

Abstract: Problem statement: Bladder cancer is a common urologic cancer and intravesical Mycobacterium bovis Bacillus Calmette-Guerin (BCG) is the mainstay in the treatment of superficial bladder cancer. However, the current BCG therapy is not desirable with respect to its efficacy and side effects. Interleukin (IL)-10, a T helper type (Th) 2 cytokine, plays an important regulatory role in bladder cancer immunosurveillance and BCG immunotherapy. Therefore, blocking IL-10 activity could be beneficial for bladder cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…Consequently, blocking IL-10 activity could enhance BCG induction of Th1 immunity and improve the outcome. Previous evidence suggested that IL-10 was upregulated in high-grade and advanced tumor stages [28] which confirms the findings of the current report. On the contrary, it has been shown that higher levels of IFN-γ might predict an enhanced T-cell mediated antitumor immune response and a better prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, blocking IL-10 activity could enhance BCG induction of Th1 immunity and improve the outcome. Previous evidence suggested that IL-10 was upregulated in high-grade and advanced tumor stages [28] which confirms the findings of the current report. On the contrary, it has been shown that higher levels of IFN-γ might predict an enhanced T-cell mediated antitumor immune response and a better prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…BCG for cancer immunotherapy activity may have its function enhanced by addition of IL10 blocking monoclonal antibody (Luo et al, 2012). Favaro et al (2012) published an interesting article where they compared and characterized the effects of intravesical BCG and/or staphylococcal enterotoxin B for non-muscle invasive bladder cancer.…”
Section: Active Therapiesmentioning
confidence: 99%
“…BCG for cancer immunotherapy activity may have its function enhanced by addition of IL10 blocking monoclonal antibody (Luo et al, 2012). Fávaro et al (2012) published an interesting article where they compared and characterized the effects of intravesical BCG and/or staphylococcal enterotoxin B for non-muscle invasive bladder cancer.…”
Section: Non-specific Therapiesmentioning
confidence: 99%